Pengaruh Pengungkapan Corporate Social Responsibility pada Nilai Perusahaan dengan Likuiditas Perusahaan sebagai Pemoderasi - Anjani, Nadya; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 24 No 2 (2018), 2018)
This study aims to obtain empirical evidence about the effect of variable disclosure of corporate social responsibility (CSR) on firm value as well as the effect of the liquidity variables as moderating variable in the relationship between the disclosure of corporate social responsibility (CSR) and firm value. CSR variables measured by the GRI guidelines G4, the variable firm value measured by Tobin's Q, while the liquidity variable is measured by calculating the current assets of each company. This type of research is quantitative. The sample is determined throughmethod non-probability withtechnique purposive sampling. The samples used in this study amounted to 31 companies that constitute the company winning the Indonesia Sustainability Reporting Award (ISRA) year from 2013 to 2016 and is a public company listed on the Indonesia Stock Exchange (BEI). This study uses Test Moderate Regression Analysis (MRA). The results of this study show that the disclosure of CSR significant positive effect on firm value and liquidity variables significant negative effect on the relationship between the disclosure of corporate social responsibility (CSR) in firm value, which means able to moderate liquidity to weaken the relationship disclosure of CSR in firm value.   Keywords: Corporate Social Responsibility Disclosure, firm value, liquidity, Indonesia Sustainability Reporting Awards.